Scorpion (Hottentotta tamulus) venom pre-exposure delays functional recovery in mice following peripheral nerve injury. - Abbas Khan; Chand Raza; Muhammad Tariq Zahid; Hafiz Faseeh Ur Rehman; Shahzad Sharif; Khajid Ullah Khan (PLoS ONE)
Scorpion sting leads to profound challenges of central nervous system (CNS) impairments such as neuro-inflammation, unconsciousness, aberrant ion channels physiology, epilepsy and may become fatal due to heart failure. However persistence of Hottentotta tamulus venom in peripheral nerves and subsequent influence on regenerative process of injured peripheral nerve remains unknown. Current study reports the persistence of H. tamulus venom components 30-days following its intraperitoneal administration in sciatic nerves (SN) of mice pre-exposed through either a single-toxin exposure (STE) or multiple-toxin exposure (MTE). Of note, venom pre-exposure delays and compromises the sensori-motor functional recovery in STE and MTE mice following standard sciatic nerve crush injury. Histological investigations of regenerating SN and gastrocnemius muscles (GCM) 14-days post crush injury exhibited reduced myelination and limited numbers of motor axons in SNs and GCM of MTE mice, respectively. Consistently, a marked reduction in expression of regeneration-promoting markers including transcription factors (such as Atf-3 and c-Jun), regeneration associated genes (such as Sprr1a and Gap-43) and ion channel proteins encoding genes (such as Scn9a and Kcc2) was observed in lumber dorsal root ganglia (DRG) and regenerating SN 14-days post crush injury. Collectively, this study reports the persistence and regeneration-inhibiting effects of H. tamulus venom in peripheral nerve of pre-exposed mice leading to compromised functional recovery.